Copper deficiency in feedlot cattle - Karapinar, Tolga; Dabak, Murat; Demirci, Yavuz; Balikci, Engin (Natl Veterinary Research Inst, 2007)
This study was conducted on 25 animals randomly selected from a herd with 40 feedlot cattle, which had poor growth, rough hair coat, and change in the colour of the hair coat. Blood samples were collected from the vena jugularis into the tubes containing Na(2)EDTA for the determination of plasma copper concentration and blood profile. Feed samples were also tested for copper, zinc, and molybdenum content. Ten healthy cattle were used as controls from different herds. In the affected group, mean plasma copper level was found to be at 6.43 mu mol/L +/- 0.01 and copper, molybdenum, and zinc levels in the diet were 15.55 ppm, 3.85 ppm, and 120 ppm, respectively. The mean plasma copper level in control animals was 13.50 pmol/L +/- 0.06). The difference was statistically significant (P < 0.001). The deficiency of copper content may result from especially high molybdenum and zinc levels in the diet. When any finding indicative of this deficiency is observed in a herd, copper status of the animals should be determined. Then, copper and especially molybdenum and zinc concentration in the diet should be examined.
Keywords: cattle; copper; deficiency; molybdenum; zinc; growth inhibition